An Idea of Hemi-abdominal Free Flap for Breast Reconstruction: A Case Report. Issue 10 (October 2020) - Tsuruta, Yuki; Miyashita, Hiroki; Kuramoto, Yukiko; Karakawa, Ryo; Suesada, Nobuko; Shibata, Tomoyoshi; Yoshimatsu, Hidehiko; Yano, Tomoyuki
Abstract : Summary: A deep inferior epigastric perforator (DIEP) flap is one of the gold standards for autologous breast reconstructions. However, this flap cannot be chosen again if asynchronous contralateral breast cancer occurs in the future. To solve this problem, we propose an idea and design for a hemi-abdominal DIEP flap. The patient was a 50-year-old woman who was suffering from right invasive ductal carcinoma. In using a hemi-abdominal DIEP flap, the poor postoperative appearance of the donor site might be a problem. To obtain a good donor site shape, we use a specific design to make the appearance of the donor site as good as possible. Specifically, we make an oblique spindle-shaped flap that can cover the deep inferior epigastric perforators, the superficial circumflex iliac artery, and the superficial inferior epigastric artery and avoid dog-ears, without passing over the median line. The flap weight was 800 g, the operating time was 6 hours and 22 minutes, and the bleeding amount was 110 ml. The patient had a minor wound infection in the donor site, and it was treated with a local wound treatment. The patient is satisfied with the result. We believe our flap design could minimize the unfavorable appearance of the donor site. This method might be suited to cases where the patients present with excess skin and fat on the abdomen, and half the abdominal tissue is enough to create the necessary volume of the breast. Although more cases and studies will be required to justify our technique, this case may show the possibility of a new option for breast reconstructions.